PNA Length Restriction of Antibacterial Activity of Peptide-PNA Conjugates in Escherichia coli Through Effects of the Inner Membrane - Goltermann, Lise; Yavari, Niloofar; Zhang, Meiqin; Ghosal, Anubrata; Nielsen, Peter E. (Frontiers in Microbiology, 2019)
Peptide Nucleic Acid (PNA)-peptide conjugates targeting essential bacterial genes are showing promise as antisense antimicrobials in drug discovery. Optimization has focused on selection of target genes and exact localization around the ribosome binding site, but surprisingly a length optimum around 10-12 nucleobases has been found. Addressing this observation, we have investigated the relationship between PNA-length, PNA-RNA duplex stability and antimicrobial activity in E. coli in more detail. For PNAs of identical length of ten nucleobases the expected reverse correlation between the thermal stability (Tm) of the PNA-RNA duplex and the MIC for single mismatched PNAs was found. Also the expected direct correlation between the length of the PNA and the PNA-RNA duplex stability was found. Nonetheless, 10-mer PNAs (in a 6-18 mer extension series of (KFF)3K- and (RXR)4 conjugates) were the most active as antisense antimicrobials in both wild type E.coli MG1655 and AS19 , suggesting that the size constraint is related to the bacterial uptake of PNA-peptide conjugates. This conclusion was supported by flow cytometry data showing higher bacterial uptake of shorter PNA fluorophore labeled conjugates . Interestingly, the size-limited uptake seems independent on outer membrane integrity (AS19), and thus the results suggest that inner membrane limits the molecular size for peptide-PNA passage.